An investigative study into the influence of a commercially available carbohydrate-protein-electrolyte beverage on short term repeated exercise performance - Roberts Justin D; Tarpey Michael D; Kass Lindsy S; Roberts Michael G (Taylor & Francis Group, 2012)
Abstract Background The purpose of this study was to undertake an independent investigation into the effects of ingesting a carbohydrate-protein-electrolyte (CPE) beverage on repeated submaximal and time-trial cycling performance. Methods Sixteen recreationally trained males (height: 1.76 ± 0.07 m; weight: 70.05 ± 7.90 kg; VO2max: 49.69 ± 4.19 ml.kg-1.min-1) performed two exercise trials separated by 7 days. Each trial comprised two bouts of 90 minutes exercise separated by a 2 hour recovery period. Each bout comprised 45 minutes exercise on a cycle-ergometer at 60%VO2max (ST), followed immediately by a 45 minute performance test (PT). Participants were randomly assigned an 8% CPE beverage or colour/taste matched placebo (PL) prior to each trial. Participants consumed 100 ml of the assigned beverage every 10 minutes during each ST, and 500 ml at 0 and 60 minutes into recovery (total caloric delivery per trial: 617.6 kcal for CPE and12.8 kcal for PL). Mean power output (W), speed (km.hr-1) and distance covered (km) were assessed throughout both trials. Expired air was sampled at 10 minute intervals throughout ST. Blood glucose and lactate were assessed during ST and recovery. Results Distance covered during ST was significantly reduced with PL by 9.12% (20.18 ± 0.28 km in ST1 v 18.34 ± 0.36 km in ST2; P = 0.0001). With CPE, distance covered, power output and average speed were maintained between ST1 and ST2. Oxygen uptake was not significantly different between ST1 and ST2, or conditions. Respiratory exchange ratio (RER) values decreased from 0.98 ± 0.02 in ST1 to 0.91 ± 0.02 in ST2 for PL (P = 0.003), supporting reduced total carbohydrate oxidation rates (P = 0.007). Mean blood glucose was maintained in CPE across ST trials, and was significantly greater than PL in ST2 (4.77 ± 0.09 mmol.L-1 for CPE compared with 4.18 ± 0.06 mmol.L-1 for PL, P < 0.001). Mean distance during PT2 was 2.96 km (or 17.1%) further with CPE than PL (P = 0.003). Mean power significantly decreased across PT with PL (134.21 ± 4.79 W and 106.90 ± 3.25 W, respectively; P < 0.04). Conclusions The use of a CPE beverage improves short-term repeated exercise and subsequent performance compared to PL. Higher rates of carbohydrate oxidation, maintenance of plasma glucose, and decreased levels of fatigue may be beneficial for secondary bouts of performance and faster recovery turnover.